Analisis rasio netrofil limfosit dan rasio platelet limfosit terhadap penanda gangguan ginjal pada penyakit systemic lupus erythematosus di RSUP dr. Wahidin Sudirohusodo tahun 2017-2018 - Evi Andriyani Lauddin; Asvin Nurulita; Darwati Muhadi (Intisari Sains Medis, 2019)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease that causes damage to several organ systems including the kidneys. The neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) continue to be developed as a marker of SLE disease activity. This study aimed to assess NLR and PLR for markers of kidney disorders in SLE.Method: A retrospective study evaluated NLR and PLR with routine urine results including proteinuria, hematuria, and casts from 40 subjects of SLE patients at Dr.Wahidin Sudirohusodo Hospital Makassar from July 2017 - July 2018. Descriptive statistical analysis, frequency distribution and Mann-Whitney statistical test.Results: NLR values were significantly higher in positive hematuria than negative hematuria, which was 7.44 compared to 3.80 (p <0.05).Conclusion: A significant relationship between increased NLR values and hematuria can be used as a marker of early occurrence of lupus nephritis even though no manifestations or signs of other kidney disorders are found.